L’identité projetée des DRH - Ivan Sainsaulieu; Éric Zufferey (Sociologies, 2018)
Swiss Human Resources Managers’ identity is paradoxal: although they are managers with a high level of assessment, they can hardly define their professional role inside their enterprise. Their collegiality is weak, their social intermediation role is not perceived as an equitable one by workers, RH assessment is not legitimate in every Executive Board, and RH wiser colleagues are skeptical about technical tools and promote face to face relations. If the myth of social progress is more and more old fashioned, HRM do not give up the idea of a prestigious past and produce a double narrative about collective professionalization and personal promotion. Living in a context of economical pressure and fast adaptation, where social matters less than commercial and financial aspects, they try to escape from skepticism, by imaging a strategic role of Boss counseling or by networking strong and light external ties, all together for instrumental, affective and symbolic purposes.